2023
DOI: 10.1186/s12866-023-02891-0
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in patients with kidney stones: a systematic review and meta-analysis

Abstract: Background Mounting evidence indicates that the gut microbiome (GMB) plays an essential role in kidney stone (KS) formation. In this study, we conducted a systematic review and meta-analysis to compare the composition of gut microbiota in kidney stone patients and healthy individuals, and further understand the role of gut microbiota in nephrolithiasis. Results Six databases were searched to find taxonomy-based comparison studies on the GMB until S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 68 publications
0
13
1
Order By: Relevance
“…Echoing previous research, our investigation also identi ed gut dysbiosis in patients with urolithiasis, characterized mainly by an increased abundance of Bacteroidota. This contrasts with earlier reports that did not nd signi cant changes in populations of Escherichia, Shigella, or Prevotella 11,12 . The consistent rise in Bacteroidota abundance emerges as a hallmark of gut dysbiosis associated with urolithiasis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Echoing previous research, our investigation also identi ed gut dysbiosis in patients with urolithiasis, characterized mainly by an increased abundance of Bacteroidota. This contrasts with earlier reports that did not nd signi cant changes in populations of Escherichia, Shigella, or Prevotella 11,12 . The consistent rise in Bacteroidota abundance emerges as a hallmark of gut dysbiosis associated with urolithiasis.…”
Section: Discussioncontrasting
confidence: 99%
“…Gut bacteria such as Lactobacillus, Bi dobacterium, Eubacterium, and Enterococcus faecalis have been implicated in the processes of oxalate absorption and stone formation 9 . Gut dysbiosis patterns, characterized by varying abundances of speci c microbial genera, have been identi ed in patients with stone disease, suggesting a complex interplay between gut microbial composition and urolithiasis 10,11 . Despite accumulating evidence of an association between the gut microbiota and stone formation, the causality of this relationship remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Although these microbiomes are difficult to detect using conventional urine culture protocols, they might influence the development of uroliths [ 39 ] by altering urinary pH to values different from those based on the cation–anion balance of the feed. Human research has shown that kidney stone patients have a characteristic gut microbiota dysbiosis that can affect stone formation [ 40 , 41 ]. The beneficial role of intestinal Oxalobacter formigenes in degrading intestinal oxalate and consequently reducing the renal oxalate burden is well-known [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The taxa at the genus level that significantly differentiated the two groups were Prevotella in the normal group and Acinetobacter in the KSD group ( 174 ). A meta-analysis including 8 studies indicated that the abundance of Bacteroides , Lactobacillus , and Prevotella showed the most significant difference in GMB between KSD patients and healthy controls ( 175 ). In UMB, Escherichia coli ( E. coli ), Lactobacillus , Staphylococcus , Streptococcus , and Klebsiella are considered vital in KSD based on evidence in vivo and in vitro ( 166 , 168 , 176 178 ).…”
Section: Association Between Circadian Rhythm Disturbance and Ksdmentioning
confidence: 99%